A cellular memory module conveys epigenetic inheritance of hedgehog expression during Drosophila wing imaginal disc development - Maurange, Cédric (Cold Spring Harbor Laboratory Press, 2002)
In Drosophila, the Trithorax-group (trxG) and Polycomb-group (PcG) proteins interact with chromosomal elements, termed Cellular Memory Modules (CMMs). By modifying chromatin, this ensures a stable heritable maintenance of the transcriptional state of developmental regulators, like the homeotic genes, that is defined embryonically. We asked whether such CMMs could also control expression of genes involved in patterning imaginal discs during larval development. Our results demonstrate that expression of the hedgehog gene, once activated, is maintained by a CMM. In addition, our experiments indicate that the switching of such CMMs to an active state during larval stages, in contrast to embryonic stages, may require specific trans-activators. Our results suggest that the patterning of cells in particular developmental fields in the imaginal discs does not only rely on external cues from morphogens, but also depends on the previous history of the cells, as the control by CMMs ensures a preformatted gene expression pattern.